Global assessment of wind erosion based on a spatially distributed RWEQ model. (February 2022) - Yang, Guocheng; Sun, Ranhao; Jing, Yongcai; Xiong, Muqi; Li, Jialei; Chen, Liding
Wind erosion is a global environmental problem and affects the sustainable use of land soil. The current efforts in wind erosion modeling mainly focus on local scales, yet very few studies have attempted to quantify the soil losses by wind on a large scale. Here, we proposed a distributed version of the revised wind erosion equation model (DRWEQ) to assess the spatial and temporal variations of wind erosion globally. The DRWEQ model used meteorological, soil, topographic, and remote sensing data to simulate global wind erosion from 2001 to 2010. The results showed that (a) the areas of wind erosion in Africa and Asia accounted for approximately 62% of the global wind erosion area but accounted for 91% of the global total soil loss; (b) global wind erosion showed a decreasing tendency during the research period – the wind erosion with a trend of intensification occupied 40.62% of the global wind erosion area while about 59.38% of the global wind erosion area showed a weakening trend; and (c) the monthly dynamics of the wind erosion were closely correlated with the combined effects of weather factors and vegetation coverage. The soil loss rates were lower in summer and reached the peak from January to April. The method presented in this study was developed based on the tradeoff of accuracy and availability of global data, and has the potential for predicting wind erosion from regional to global scales.